1975
DOI: 10.1152/jappl.1975.39.6.976
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment in networks of pulmonary capillaries

Abstract: To improve our understanding of the pressure-flow characteristics of pulmonary capillaries, we analyzed by means of computer stimulation a theoretical model composed of 50 interconnected nonlinear elements. Each element required a critical pressure across it before flow occurred and there was a subsequent linear pressure-flow region whose slope, or resistance, could be related to the transmural pressure of the element ("distensibility"). The critical pressures and resistances of each element of the network wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
17
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…In a complex network, however, pressure gradients between feeders and drainers could fall to zero as elements in other parts of the network are recruited, which would cause that element to close (derecruit). In other circumstances, the pressure in the drainer could exceed the feeder pressure, thus reversing the direction of flow, as predicted by West et al (32) and observed in these experiments.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…In a complex network, however, pressure gradients between feeders and drainers could fall to zero as elements in other parts of the network are recruited, which would cause that element to close (derecruit). In other circumstances, the pressure in the drainer could exceed the feeder pressure, thus reversing the direction of flow, as predicted by West et al (32) and observed in these experiments.…”
supporting
confidence: 81%
“…The scatter in the data of Godbey et al as capillaries recruited suggests confirmation of the Warrell data, i.e., that capillary recruitment could be heterogeneous. West et al (32), using an elegant computer model, deduced that recruitment in a network of resistors could be heterogeneous. Nevertheless, the variety of models, each based on credible evidence, does not present a coherent picture of how alveolar capillaries recruit.…”
mentioning
confidence: 99%
“…65(9): 965-970, 2003 In normal dogs, an increase in pulmonary blood flow is associated with a decrease in pulmonary vascular resistance without a marked elevation in pulmonary arterial pressure [14,15]. The reduction in pulmonary vascular resistance is generally considered to be due to capillary recruitment and/ or dilatation [6,19]. In dogs with heartworm disease, however, the reduction in pulmonary vascular resistance that accompanies an increase in cardiac output is smaller in magnitude than normal dogs [12,13].…”
mentioning
confidence: 99%
“…The reduction in pulmonary vascular resistance is generally considered to be due to capillary recruitment and/ or dilatation [6,19]. In dogs with heartworm disease, however, the reduction in pulmonary vascular resistance that accompanies an increase in cardiac output is smaller in magnitude than normal dogs [12,13].…”
mentioning
confidence: 99%
“…Thereafter, PA flow and pressure were recorded during irregular pacing (R-R intervals uniformly distributed reduction of the perfused pulmonary vascular bed in unilateral lung is expected to double both RP and ZC and halve CP, 12 the pulmonary circulation is unique in that a recruitment phenomenon, that is, opening up of previously closed peripheral vessels, occurs when PA flow and pressure increase. 13, 14 As the recruitment phenomenon likely compensates for the increase in RP with little impact on ZC, RP may not increase proportionally to ZC when a large volume of the pulmonary vascular bed is lost, such as in the case of acute PTE in the proximal PA. The fact that the ratio of ZC to RP in the pulmonary circulation is not as small as that in the systemic circulation 15,16 also indicates the importance of assessing both ZC and RP in the pulmonary circulation.…”
mentioning
confidence: 99%